Of Gods and Men (and Dogs): Review of Laura Hobgood-Oster, A Dog’s History of the World: Canines and the Domestication of Humans - Gordon, Joan (Humanimalia, 2014)
Laura Hobgood-Oster. A Dog’s History of the World: Canines and the Domestication of Humans. Waco, TX: Baylor UP, 2014. 188 pp. 29.94 hc.